2011
DOI: 10.1161/strokeaha.110.611459
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Stenting and Angioplasty of Symptomatic Extracranial Vertebral Artery Stenosis

Abstract: Background and Purpose-Extracranial vertebral artery stenosis (ECVAS) is common among patients with ischemic stroke. Despite the limited knowledge of the natural history of patients with symptomatic vertebral disease, endovascular revascularization techniques are now utilized in clinical practice. We sought to determine the risk of endovascular treatment for ECVAS with a systematic review of the literature. Methods-A search strategy was used using the terms "stenting," "vertebral," "ostium," "origin," and "ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 43 publications
6
89
0
3
Order By: Relevance
“…3,9,14,21) However, a systematic review of percutaneous revascularization of extracranial VA stenosis found no differences in periprocedural stroke rates with or without protection devices. 16) Similarly, the endovascular treatment without an embolic protection device performed in our case did not result in procedural thromboembolic complication.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…3,9,14,21) However, a systematic review of percutaneous revascularization of extracranial VA stenosis found no differences in periprocedural stroke rates with or without protection devices. 16) Similarly, the endovascular treatment without an embolic protection device performed in our case did not result in procedural thromboembolic complication.…”
Section: Discussionsupporting
confidence: 64%
“…16) Stenting of a longsegment extracranial VA occlusion was also reported. 5) However, to our knowledge, no reports have described endovascular angioplasty of VA origin occlusion without visualization of the stump of the artery ostium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the effect of novel agents, including antiplatelet agents and statins, on altering the natural history of these lesions is less well studied. Recent attempts at the use of stenting and/or angioplasty for these lesions has produced mixed results 1,8,26,27 and significant rates of restenosis, ranging from 11% for drug-eluting stents to more than 30% for bare-metal stents.Microsurgical revascularization of the proximal VA has been well described, but the majority of published series included small patient populations and short follow-up ObJect Despite advances in medical management and endovascular therapies, including the introduction of statins, antiplatelet agents, and drug-eluting stents, some patients experience medically refractory vertebrobasilar insufficiency and may benefit from robust surgical revascularization. The aim of this study was to evaluate such patients after surgical revascularization, emphasizing long-term outcomes and rates of complications.…”
mentioning
confidence: 99%